TRANSFORMING MENTAL HEALTH IN PAKISTAN THROUGH THE 26TH NATIONAL PSYCHIATRIC CONFERENCE - Zain Ullah Khan; Shoaib Ahmed Kashani; Mujeebullah Khan Doutani (Journal of Pakistan Psychiatric Society, 2025)
Mental health has increasingly become a central issue of discussion across the globe, and Pakistan is no exception. With a population exceeding 240 million people, the country faces numerous challenges ranging from poverty, unemployment, and displacement to natural disasters, political instability, and the aftereffects of global crises such as the COVID-19 pandemic. These challenges not only affect physical health and economic progress but also deeply impact the psychological well-being of individuals and communities.